Immune reconstitution inflammatory syndrome from Penicillium marneffei in an HIV-infected child: A case report and review of literature - Tavitiya Sudjaritruk (2018)
Backgrounds: Disseminated Penicillium marneffei infection is one of the most common HIV-related opportunistic infections in Southeast Asia. Immune reconstitution inflammatory syndrome (IRIS) is a complication related to antiretroviral therapy (ART)-induced immune restoration. The aim of this report is to present a case of HIV-infected child who developed an unmasking type of IRIS caused by disseminated P. marneffei infection after ART initiation.Case presentation: A 14-year-old Thai HIV-infected girl presented with high-grade fever, multiple painful ulcerated oral lesions, generalized non-pruritic erythrematous skin papules and nodules with central umbilication, and multiple swollen, warm, and tender joints 8 weeks after ART initiation. At that time, her CD4 + cell count was 7.2% or 39 cells/mm 3. On admission, her repeated CD4 + cell count was 11% or 51 cells/mm 3 and her plasma HIV-RNA level was < 50 copies/mL. Her skin biopsy showed necrotizing histiocytic granuloma formation with neutrophilic infiltration in the upper and reticular dermis. Tissue sections stained with hematoxylin and eosin (H&E), periodic acid-Schiff (PAS), and Grocott methenamine silver (GMS) stain revealed numerous intracellular and extracellular, round to oval, elongated, thin-walled yeast cells with central septation. The hemoculture, bone marrow culture, and skin culture revealed no growth of fungus or bacteria. Our patient responded well to intravenous amphotericin B followed by oral itraconazole. She fully recovered after 4-month antifungal treatment without evidence of recurrence of disease.Conclusions: IRIS from P. marneffei in HIV-infected people is rare. Appropriate recognition and properly treatment is important for a good prognosis. © 2012 Sudjaritruk et al; licensee BioMed Central Ltd.